Strategi Pengawasan Langsung Kepala Desa Dalam Program Dasa Wisma Di Desa Hutabaringin Tombang Bustak (TB) - Affan Al Quddus; Febriyanti Alda Lubis (Universitas Muhammadiyah Sumatera Utara, 2023)
Dasa Wisma is a tithing group from a community that will later play an active role in launching PKK programs aimed at family resilience which has been planned by the community itself. This means that the activities carried out in Dasa Wisma are a strategy to increase participation from the community or as a place for social activities to take place which aims to strengthen family resilience in the community. This study used a descriptive method with qualitative data analysis, namely data collected from interviews with informants through open interviews and documentation with the Village Government and the Head of the PKK. The results showed that the development of community potential in Huta Baringin TB Village, Mandailing Natal Regency had been carried out well, although there were still some obstacles, such as funding needs, and programs that had not been fully implemented. The aim of the Dasa Wisma group is to help smooth the main tasks and the village PKK program. Its activities are directed at improving family health.